2019
DOI: 10.1371/journal.pone.0226066
|View full text |Cite
|
Sign up to set email alerts
|

Classification of flavors in cigarillos and little cigars and their variable cellular and acellular oxidative and cytotoxic responses

Abstract: Flavored tobacco products are increasing in popularity but remain unregulated, with the exception of the ban on flavored conventional cigarettes. Lack of regulation of cigarillos and little cigars allows vendors to have their own version of popular flavors, each with different chemical components. A new classification system was created for flavored cigars in order to easily communicate our results with the scientific community. To understand the physicochemical characteristics of flavored little cigars and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Research investigating how flavoring chemicals affect ROS generation in e-cigarette generated aerosols has been explored minimally; however, a few recent studies have delved into the dependence that ROS generation from e-cigarettes may have on flavoring chemicals. Our study found that ROS levels generated from cigar/cigarillo smoke varied among different flavors [ 16 ]. Regarding studies conducted with e-cigarettes, another study found that ROS generation within the aerosols generated from cartridge-based e-cigarette devices was highly dependent on the vendor, puffing pattern, voltage, and the flavor of the cartridge-based e-cigarette device used [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating how flavoring chemicals affect ROS generation in e-cigarette generated aerosols has been explored minimally; however, a few recent studies have delved into the dependence that ROS generation from e-cigarettes may have on flavoring chemicals. Our study found that ROS levels generated from cigar/cigarillo smoke varied among different flavors [ 16 ]. Regarding studies conducted with e-cigarettes, another study found that ROS generation within the aerosols generated from cartridge-based e-cigarette devices was highly dependent on the vendor, puffing pattern, voltage, and the flavor of the cartridge-based e-cigarette device used [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, e-liquids are composed of propylene glycol (PG) and/or vegetable glycerin (VG), with varying concentrations of nicotine (up to 100 mg/mL). Flavoring chemicals are added as additives in e-liquids and pods that enhance the taste and reduce throat hit, however they tend to attract the younger generation unexpectedly [3,4]. While PG and VG are considered safe in foodgrade products, adverse health effects have been reported from these substances when they serve as e-cig vehicles [5].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, e-liquids are composed of propylene glycol (PG) and/or vegetable glycerin (VG), with varying concentrations of nicotine (up to 100 mg/mL). Flavoring chemicals are added as additives in e-liquids and pods that enhance the taste and reduce throat hit, however they tend to attract younger generation unexpectedly [3,4]. While PG and VG are considered safe in food-grade products, adverse health effects have been reported from these substances when they serve as e-cig vehicles [5].…”
Section: Introductionmentioning
confidence: 99%